Determinants of customers' choice of selected fast food restaurants - Tuble, Amelia C.; Lopez, Ma. Belinda V. (1992., 1992)
The study investigated some of the factors that may influence customers' choice of the selected fast food restaurants, namely: their personal characteristics, their eating habits and practices, their current health and nutrition concerns and their attitudes toward restaurant attributes. A one-shot survey was conducted among 300 customers in three selected fast food chains in Metro Manila. Purposive sampling was used in selecting the respondent companies based on the study released by the Mahal Kong Pilipinas Foundation's listing of the top 1000 Philippine Corporations, 1988. The companies selected were among the top ten companies in the industry. Two were multi-national companies and one was Filipino-owned. The respondents consisted of the daily walk-in Filipino customers aged 7 to 70 years old, who were chosen using stratified random sampling. Results of the correlation analysis using the chi-square, contingency coefficient and the t-tests showed that the age and the sex of customers influenced their choice of fast food restaurant. The perception of the male and female customers on the necessity of nutrition information in menus and they type of food that they avoided ordering influenced their choice of fast food restaurant. Customers' attitudes toward restaurant attributes like the portion size of the food served, the provision of an adequate parking space, the container boxes for take home item, and the prices of food and geographical location influenced their choice of fast food restaurant. Of the six restaurant attributes included in the study, the place came out as a determinant of the customers' choice of fast food restaurant. Other restaurant attribute which did not come out as a determinant were: the food, the service, the atmosphere, the promotion and the price. The findings of the study warrant that a similar study be undertaken to follow-up and keep abreast of changes in customers' personal characteristics, eating habits and practices, nutrition and health concerns and their attitudes toward restaurant attributes. It is suggested that nutritionist-dietitians should include commercial food services in their efforts in disseminating nutrition information. Future studies should include weather conditions, special occasions, payday variations in the menu offering which may also influence customers' decision in choosing fast food restaurants. Considering the time and the money spent on food by the operators and its impact on the health and well-being of the people, it is further recommended that the government policy-makers should monitor thee establishments, evaluate their menu offering and recommend improvements or set rules for the provision of nutrition information.
Thesis (M. Food Service Administartion)--University of the Philippines, Diliman.
Typescript.
Keywords: Fast food restaurants -- Philippines -- Manila metropolitan area; Consumers -- Philippines -- Manila metropolitan area -- Attitudes